Analysis of Networker's Language Disability in the Comments Column Instagram Account @Medantalk - Siti Nurhaliza Chaniago; Yusni Khairul Amri (Britain International for Academic Research (BIAR) Publisher, 2023)
Social media is part of communication media. Instagram is one of the social media that is being loved by many people. Its use is also very diverse, ranging from children to the elderly. Social media, which focuses on photo and video sharing platforms, has skyrocketed in popularity, but it is undeniable that the various impacts that can be caused are due to responses from each netizen as a social media user, for example the emergence of the use of impolite language which causes a violation of the principle of politeness speak. The results of this analysis indicate that there is impoliteness in the language of netizens in the comments column of the @medantalk Instragram account, causing a violation of the principle of politeness in language put forward by Leech. The politeness principle put forward by Leech consists of six maxims, namely the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of modesty, the maxim of agreement and the maxim of sympathy.